1998
DOI: 10.1021/jf980294w
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Spatial Distribution of Flavonol and Peroxidase in Onion Bulbs and Stability of Flavonol Glucosides during Boiling of the Scales

Abstract: Two major flavonol glycosides [quercetin 3,4‘-diglucoside (F1) and quercetin 4‘-monoglucoside (F2)] and a flavonol aglycon quercetin were mainly localized in the abaxial epidermis of scales. Their contents increased on aging. Peroxidase in scales oxidized flavonols in the order quercetin ≫ F2 > isoquercetin ≫ F1, and the activity was higher in the outer than in the inner scales. These results suggest that the enzyme can participate in the formation of defense substances against infection and brown compounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 34 publications
5
96
0
Order By: Relevance
“…Since polyphenols are normally ingested by mouth as vegetables and fruits, elucidation of their metabolism in the oral cavity is also important. In previous papers, we reported that when onion soup, which contains quercetin glucosides (Hirota et al, 1998(Hirota et al, , 1999, is ingested, the glucosides are hydrolyzed to the aglycone quercetin, and that quercetin is degraded in the oral cavity (Hirota et al, 2001). The degradation is also observed when quercetin is added to collected saliva with and without externally added H 2 O 2 .…”
mentioning
confidence: 99%
“…Since polyphenols are normally ingested by mouth as vegetables and fruits, elucidation of their metabolism in the oral cavity is also important. In previous papers, we reported that when onion soup, which contains quercetin glucosides (Hirota et al, 1998(Hirota et al, , 1999, is ingested, the glucosides are hydrolyzed to the aglycone quercetin, and that quercetin is degraded in the oral cavity (Hirota et al, 2001). The degradation is also observed when quercetin is added to collected saliva with and without externally added H 2 O 2 .…”
mentioning
confidence: 99%
“…The reaction was initiated by adding 0.8 mL H 2 O 2 (1 mM in phosphate buffer, pH 7). The decrease in absorbance at 370 nm (λ max of quercetin) was recorded using a HP8452A diode array spectrophotometer (Hirota et al 1998). One peroxidase unit was defined as ΔA 370 min −1 and the specific activity (υ s ) as U mg −1 of protein.…”
Section: Methodsmentioning
confidence: 99%
“…(Osaka, Japan). Quercetin 4¢-monoglucoside and quercetin 3,4¢-diglucoside from onion bulbs were prepared by thin-layer chromatography (silica gel) and the concentrations were estimated from the absorbance at 360 nm using isoquercitrin as a standard as reported previously (Hirota et al, 1998).…”
Section: Methodsmentioning
confidence: 99%